Fritz Zwicky and the earliest prediction of dark matter. (July 2021) - Zwicky, Barbarina; Meyling, Johannes; Appell, David
Abstract : In response to the feature article "The 10 greatest predictions in physics" by the science writer David Appell (January pp36–40), which included Vera Rubin and Kent Ford Jr's prediction that dark matter can account for the unusual motion of outer stars in the Andromeda galaxy.